The Effect of Duration in Providing Kangaroo Mother Care (KMC) on Mother's Psychological Function in Low Birth Weight Babies at Private Midwife Practice Millatin Khusniyati, S.Tr.Keb Jepara - Triana Widiastuti (Journal of Global Research in Public Health, 2023)
A low birth weight babies, in addition to have an impact on physiological function disorders, will also affect the mother's psychology. Management is carried out by providing kangaroo mother care (KMC). There were 16 cases of low birth weight babies in April. The purpose of the study was to determine the effect of  Kangaroo mother care (KMC) time duration with Infant Physiological and Maternal Psychological Functions on Low Birth Weight Infants in Private Midwife Practice Millatin Khusniyati, S.Tr.Keb Jepara. This type of research is quantitative, quasi-experimental research design with two group post test design. There were 16 low birth weight babbies as the sample. The intervention was carried out once for an hour and two hours within 1 day. Data was analyzed by using Mann Whitney. The results of the study states there was no difference in the psychological status of mothers given KMC with a duration of 1 and 2 hours (0.626> 0.05). It was concluded that there was no difference in the psychological status of mothers given KMC with a duration of 1 and 2 hours. These results can provide information, and practice giving KMC at a duration of 1 and 2 hours to psychological functions, through counseling and practics, at posyandu activities.